GAYA NGURAH PARSUA MENGUNGKAPKANKRITIKLINGKUNGAN MELALUI SAJAK“POTRET POHON AIR MATA” - Dody Satrya Wirandika, Gede (Humanis, 2015)
Ngurah Parsua is a poet who care about the environment. Ideas, views, and criticisms of the environment conveyed through poetry. As well as rhyme “Potret Pohon Air Mata” contained criticisms of the destruction of the environment today. Diction in his poem can be said to have high aesthetic value, because it uses poetic language which contains a figure of speech. Ngurah Parsua also uses diction sad like the word ‘tear’ that can be found in each poem. Through word ‘tears’ he depicts the sufferings of this present environment.
Keywords: criticism, environment, diction